2001
DOI: 10.1152/ajpgi.2001.280.4.g701
|View full text |Cite
|
Sign up to set email alerts
|

Expression and immunolocalization of aquaporin water channels in rat exocrine pancreas

Abstract: Both the acinar and ductal cells of the pancreas secrete a near-isotonic fluid and may thus be sites of aquaporin (AQP) water channel expression. Northern blot analysis of mRNA from whole rat pancreas revealed high levels of AQP1 and AQP8 expression, whereas lower levels of AQP4 and AQP5 expression were just detectable by RT-PCR Southern blot analysis. Immunohistochemistry showed that AQP1 is localized in the microvasculature, whereas AQP8 is confined to the apical pole of the acinar cells. No labeling of acin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 34 publications
6
55
1
Order By: Relevance
“…In this case, it is likely that HgCl 2 in addition to altering the concentration gradient was interfering also with regulation of cell volume [23]. We observed extreme cell swelling under the microscope in the present investigation, especially at the higher concentration of 100 mM.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…In this case, it is likely that HgCl 2 in addition to altering the concentration gradient was interfering also with regulation of cell volume [23]. We observed extreme cell swelling under the microscope in the present investigation, especially at the higher concentration of 100 mM.…”
Section: Discussionsupporting
confidence: 41%
“…Nerve and muscle membranes are also affected by mercuric chloride (HgCl 2 ) and MeHg [3,6,7,12,25,34,39], and voltage-activated calcium [10,28,29,37,41,46], sodium [38], chloride [12,23] and potassium (K + ) [11,15,18,38] channels are similarly suppressed. The GABA receptor channel [5,22,36], the Na, K-ATPase pump and excitatory amino acid receptors [31] have also been the target of Hg 2 + modulation.…”
Section: Introductionmentioning
confidence: 99%
“…d-cAMP caused a significant increase in canalicular secretion, and this effect could be completely abrogated by both Me 2 SO and phloretin. *, p Ͻ 0.05. sion has also been demonstrated on the luminal side of seminiferous tubules, the apical membrane of pancreatic acinar cells, and in both absorptive epithelia of the colon and acinar cells of the salivary gland; whether AQP8 in these tissues is also regulated by a trafficking mechanism has not been explored (10,(33)(34)(35)(36).…”
Section: Fig 7 D-camp-induced Bile Secretionmentioning
confidence: 99%
“…Here we report the generation of MDCK-II cells stably transfected with AQP5 (RW5 cells) or AQP8 (RW8 cells). Cell culture systems for the study of AQP5 and AQP8 sorting are of physiological import as (i) AQP5 has been shown to play a role in salivary secretion (3,16), (ii) the missorting of AQP5 occurring in patients suffering from Sjogren's syndrome has been suggested to contribute to the disease-related deficiency in fluid secretion (13,14), and (iii) AQP8 has been suggested to play a role in pancreatic (17), liver (18), and gastrointestinal (19) secretion. This is the first report of polarized epithelial cell cultures with AQPs 5 and 8 expressed functionally and in a polarized fashion, and the first evidence of the basolateral sorting of AQP8 in a polarized epithelial cell.…”
mentioning
confidence: 99%